2005
DOI: 10.1038/ncb1268
|View full text |Cite
|
Sign up to set email alerts
|

S-nitrosylated GAPDH initiates apoptotic cell death by nuclear translocation following Siah1 binding

Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) influences cytotoxicity, translocating to the nucleus during apoptosis. Here we report a signalling pathway in which nitric oxide (NO) generation that follows apoptotic stimulation elicits S-nitrosylation of GAPDH, which triggers binding to Siah1 (an E3 ubiquitin ligase), nuclear translocation and apoptosis. S-nitrosylation of GAPDH augments its binding to Siah1, whose nuclear localization signal mediates translocation of GAPDH. GAPDH stabilizes Siah1, facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
965
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 974 publications
(1,002 citation statements)
references
References 48 publications
31
965
3
3
Order By: Relevance
“…These include the transcriptional regulation of histone gene expression (Zheng et al, 2003), the role of GAPDH in nuclear membrane fusion (Nakagawa et al, 2003), in the modulation of telomere structure (Sundararaj et al, 2004), in the recognition of fraudulent nucleotides in DNA arising from cancer chemotherapy (Krynetski et al, 2003) and in triggering apoptosis (Chuang et al, 2005;Hara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…These include the transcriptional regulation of histone gene expression (Zheng et al, 2003), the role of GAPDH in nuclear membrane fusion (Nakagawa et al, 2003), in the modulation of telomere structure (Sundararaj et al, 2004), in the recognition of fraudulent nucleotides in DNA arising from cancer chemotherapy (Krynetski et al, 2003) and in triggering apoptosis (Chuang et al, 2005;Hara et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter scenario, glyceraldehyde-3-dehydrogenase (GADPH) is the target of S-nitrosylation of catalytic site cysteine 150, which in turn causes binding of the E3 ligase, Siah1 to GAPDH, and stabilizes Siah1, which is otherwise rapidly turned over. The SNO-GAPDH-Siah1 complex can then translocate to the nucleus, where Siah1 targets nuclear proteins for degradation [184,185].…”
Section: Regulation Of Molecular Adaptors and Chaperonesmentioning
confidence: 99%
“…46,47 Our group first identified the physiological relevance of S-nitrosylation by showing that NO and related RNS exert paradoxical effects via redox-based mechanisms -NO is neuroprotective via S-nitrosylation of NMDA receptors (as well as other subsequently discovered targets, including caspases), and yet can also be neurodestructive by formation of peroxynitrite (or, as later discovered, reaction with additional molecules such as parkin, PDI, GAPDH, and MMP-9) (Figure 1). 6,8,9,12,14,16,17,[19][20][21][22]48 Over the past decade, accumulating evidence has suggested that S-nitrosylation can regulate the biological activity of a great variety of proteins, in some ways akin to phosphorylation. 10,[49][50][51][52][53][54] Chemically, NO is often a good 'leaving group,' facilitating further oxidation of critical thiol to disulfide bonds among neighboring (vicinal) cysteine residues or, via reaction with ROS, to sulfenic (ÀSOH), sulfinic (ÀSO 2 H), or sulfonic (ÀSO 3 H) acid derivatization of the protein.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
“…Recent findings, however, have shed light on molecular events underlying this relationship. Specifically, we and other groups have recently mounted physiological and chemical evidence that S-nitrosylation enhances (1) neuronal survival by inhibiting the activities of (a) NMDA receptors and (b) caspases, or (2) neuronal cell injury by regulating the (a) ubiquitin E3 ligase activity of parkin, 17,18,20 (b) chaperone and isomerase activities of PDI, 19 (c) nuclear translocation of GAPDH, 21 and (d) activity of MMP-9. 22 In particular, S-nitrosylation of PDI and parkin can regulate protein misfolding and neurotoxicity in models of neurodegenerative disorders, and SNO-PDI, or SNO-parkin has been found in human postmortem brain tissue from patients with neurodegenerative conditions.…”
Section: Protein S-nitrosylation Affects Neuronal Survivalmentioning
confidence: 99%
See 1 more Smart Citation